Voluntary Environmental Regulations and Firm Innovation in China - Zhang, Shaojie (Asian Journal of Economics and Empirical Research, 2020)
The world is fighting the issue of increasing levels of pollution and the detrimental effects of the ecological imprints of the business industry. Pollution and other environmental issues are causing the environment to deteriorate; however, this has also led to an increased interest in the protection of the environment. The Porter hypothesis has stimulated a long debate on whether organizational regulations can lead to changes in a firm’s innovation. Building on these theories, this study evaluates the effect of voluntary environmental regulations (VERs) on the innovation of Chinese firms. For this purpose, the study uses a dichotomous dependent variable. The proxy variables used for evaluating the innovative performance of firms are the average investments made for research and development (R&D) activities, which are evaluated on the basis of investments made and the decision to invest in innovation activities. VERs were evaluated using applications for the ISO 14000 certification. The study uses firm level variables to answer the research questions, as well as control variables such as firm size, profitability, degree of competition, and high technology industry. The results of the estimations reveal that the impact of environmental regulations (ERs) is positive and significant in terms of the innovation output of the firms under consideration. Moreover, the results also highlight the fact that large firms with high levels of profitability and a presence in the technology sector are more adept at introducing innovative activities. The study also provides some policy implications.